339 Management of Blunt Cerebrovascular Injuries Simplified: Experience With an Aspirin-Based Approach. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Catapano, Joshua; Israr, Sharjeel; Ducruet, Andrew F; Albuquerque, Felipe; Whiting, Alex; Rubalcava, Nathan; Snyder, Laura A; Weinberg, Jordan; Zabramski, Joseph M
Abstract: INTRODUCTION: Although the optimal antithrombotic therapy for extracranial blunt cerebrovascular injury (BCVI) remains unknown, anticoagulation with intravenous heparin has been favored. In the current decade, however, we transitioned our practice to an aspirin-based approach. The purpose of this study was to review the efficacy and bleeding risk of this strategy for BCVI management. METHODS: Patients with BCVI were identified at a level 1 trauma center between 2010 and 2017. Imaging was reviewed and electronic medical records were examined for patient information including demographics, injury type, therapy, complications, outcomes, and follow-up. RESULTS: Over the study period, 13 578 patients were admitted following blunt trauma with 94 (0.7%) patients having confirmed BCVI. Average age was 42 yr, with 68 males (72%). Mean Injury Severity Score and Glasgow Coma Score were 27 and 10, respectively. A total of 130 vessels were found to have been injured, with a predominance of vertebral artery injuries (78, 60%). The majority of vessels sustained Biffl grade I or II injury (53 (38%) and 38 (29%) respectively). Twenty-six (28%) patients died during hospitalization. Twelve (13%) patients suffered an ischemic event; 3 following initial diagnosis. Aspirin was primary treatment for 56 (59.6%) patients, 30 (32%) patients received no treatment, and 7 (7.4%) underwent endovascular therapy. FOur (7%) patients treated with aspirin suffered a bleeding complication (2 with progression of intracranial hemorrhage and 2 with GI bleed). Of the 68 survivors, 33(48.5%) patients had follow-up imaging with a mean follow-up of 36 d and 2(6%) patients had progression of injury. Fifteen (46%) patients had improvement. CONCLUSION: An aspirin-based management strategy for BCVI was observed to be both efficacious and relatively safe. The incidence of ischemic events was lower than the majority of previous reports, as was the risk of bleeding. An aspirin-based approach is both simple and effective, and may be the preferred antithrombotic treatment for BCVI.